MXene Materials: Effect of Synthesis on Quality, Electronic Properties and Environmental Stability of Individual Monolayer Ti3C2 MXene Flakes (Adv. Electron. Mater. 12/2016). (December 2016) - Lipatov, Alexey; Alhabeb, Mohamed; Lukatskaya, Maria R.; Boson, Alex; Gogotsi, Yury; Sinitskii, Alexander
Abstract : In article number 1600255, A. Lipatov et al. report a synthetic method for high‐quality monolayer flakes of Ti3 C2 Tx, the most widely studied MXene material, and the investigation of their electrical properties, environmental stability and kinetics of oxidation in air. Individual monolayer Ti3 C2 Tx flakes have electrical conductivity of 4600 ± 1100 S cm −1, field‐effect electron mobility of 2.6 ± 0.7 cm 2 V −1 s −1, and remain highly conductive even after exposure to air for more than 24 h.